2004
DOI: 10.1164/rccm.200307-959oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment with Dornase Alpha on Airway Inflammation in Patients with Cystic Fibrosis

Abstract: Recombinant human deoxyribonuclease (rhDNase) has been shown to improve lung function and reduce the number of pulmonary exacerbations in patients with cystic fibrosis (CF), but its long-term effect on airway inflammation remains unknown. In this study, we used bronchoalveolar lavage (BAL) to investigate the long-term effect of rhDNase on inflammation in patients with CF having mild lung disease. A total of 105 patients with CF (> or =5 years of age) having normal lung function were randomized to receive rhDNa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
98
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 39 publications
(43 reference statements)
5
98
0
3
Order By: Relevance
“…We randomly and consecutively recruited children from our clinics and did not target specific individuals for enrollment. The rate of decline in FEV 1 in our cohort closely approximated the rate observed in all school-age children with CF followed at our center and is reasonably comparable to that reported in other recent studies of children and adolescents with CF (13,22,28,29). This suggests that our small study cohort relatively closely reflects the larger population of school-age children with CF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We randomly and consecutively recruited children from our clinics and did not target specific individuals for enrollment. The rate of decline in FEV 1 in our cohort closely approximated the rate observed in all school-age children with CF followed at our center and is reasonably comparable to that reported in other recent studies of children and adolescents with CF (13,22,28,29). This suggests that our small study cohort relatively closely reflects the larger population of school-age children with CF.…”
Section: Discussionsupporting
confidence: 89%
“…In a single-center study of older subjects with CF with worse lung function than that in our study cohort, changes in sputum DNA concentrations (but not IL-8 or myeloperoxidase concentrations) at two discrete time points within 1 year correlated with changes in lung function (21). Another study that used bronchoalveolar lavage (BAL) rather than sputum to investigate the long-term effect of recombinant human DNase on inflammation in a study cohort similar to ours (mainly children with CF with mild lung disease), reported a significant increase in BAL biomarkers of airway inflammation (neutrophil counts, free neutrophil elastase, and IL-8) in untreated subjects, whereas levels of these biomarkers remained relatively unchanged in patients treated with DNase (22). In this same study, patients with a normal percentage of neutrophils in BAL fluid at baseline did not show a decline in lung function over a 3-year period, a finding supporting the view that airway inflammation has a negative impact on subsequent lung disease progression in CF.…”
Section: Discussionmentioning
confidence: 64%
“…Despite several lines of pathophysiological evidence to support the concept of an overwhelming pro-inflammatory response in CF airways [2], only a few clinical studies have successfully established anti-inflammatory strategies in patients with CF lung disease, such as the application of ibuprofen [4][5][6] and recombinant human DNase [7]. Other studies have demonstrated the ineffectiveness or the occurrence of adverse side-effects of approaches involving inhaled steroids [8] and a leukotriene (LT)B 4 antagonist [9].…”
mentioning
confidence: 99%
“…This mechanism is supposed to reduce the induced chance of infection exacerbations [12,13,18]. Direct anti-inflammatory effects of rhDNAse have also been described, for instance reflected by a decrease in IL-8 [27].…”
Section: Discussionmentioning
confidence: 99%